A Family-Focused, Sibling-Synchronous Intervention in Borno State, Nigeria: Exploring the Impact on Family Functioning and Household Gender Roles - Seff, Ilana (Journal of family violence, 2023)
Abstract PurposeThe ways family members engage and communicate with each other has significant impacts on well-being and coping strategies in the face of adversity, but there is a dearth of studies examining family functioning programming in humanitarian settings, particularly programs that incorporate a gender lens and engage multiple family members and genders. This study evaluates the Sibling Support for Adolescent Girls in Emergencies (SSAGE) intervention to understand the impact of gender transformative family programming on family functioning.MethodsThe 12-week SSAGE program engaged adolescent girls, their adolescent brothers, and their caregivers in Northeast Nigeria in synchronous sessions stratified by gender and age, with curricula exploring topics including gender-based violence, healthy relationships, and positive parenting. The two-week, post-intervention qualitative evaluation consisted of key informant and paired interviews, participatory research activities, focus group discussions, and in-depth interviews with 90 program participants and 12 program staff/mentors to understand the intervention’s impact on attitudes and behaviors around family gender roles.ResultsFindings revealed improved communication within families, bolstered by mentors’ encouragement to discuss program topics within households, and caregivers’ and siblings’ shift toward the use of healthier, non-corporal behavior control methods. Families described how the intervention promoted conversations around gendered issues including early marriage, education, employment, and puberty.Results This study builds the evidence base for gender transformative family functioning programming in humanitarian contexts. Practitioners should work to ensure safety of women and girls in future programming, particularly by focusing on communication skills and promoting gender norms change both within households and the community.